Student’s Perception of Physical Learning Model through Elementary School Level Games of North Musi Rawas Regency - Puspitasari, Yuliani; Lanos, Muhsana El Cintami; Handayani, Widya (Journal of Social Work and Science Education, 2023)
This study aims to determine students’ perceptions of physical education learning models through games based on (1) Perceptions of physical education learning knowledge, (2) Perceptions of teacher teaching styles, (3) Perceptions of easy-to-use media, (4) Perceptions of interest in learning physical education, (5) Perceptions about the need to develop a physical education learning model through games. This research is descriptive quantitative research. The results of this study indicate that (1) the perception of physical education learning knowledge obtained a score of 90.50% in the very good category, (2) the perception of the teacher’s teaching style obtained a value of 75.50% in the good category, (3) the perception of the media used is easy used to obtain a score of 87% in the very good category, (4) Perceptions about interest in learning physical education obtained a value of 97% in the very good category, (5) Perceptions about the need to develop a learning model for basic volleyball techniques through a play approach obtained a value of 100% in the category very well, which means students agree if the development of physical education learning models through games is developed. The results of this study indicate that students’ perceptions of the development of physical education learning models through games in elementary schools in North Musi Rawas Regency are positive, for this reason it is necessary to develop physical education learning models through games.